Doege–Potter syndrome due to endothoracic solitary hypoglycemic fibrous tumor - Lopez- Hinostroza, Madaleine (2022)
Doege– Potter syndrome leads to severe and sustained symptomatic hypoglyce-mia and is associated with the solitary fibrous tumor. It is a rare cause, and its diagnosis requires a clinical suspicion and other markers such as insulin- like growth factor II. Here, we describe a case of a patient with intrathoracic tumor and hypoglycemia.